2022
DOI: 10.3390/pharmaceutics14081634
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing Based on Protozoan Proteome: In Vitro Evaluation of In Silico Screened Compounds against Toxoplasma gondii

Abstract: Toxoplasma gondii is a protozoan that infects up to a third of the world’s population. This parasite can cause serious problems, especially if a woman is infected during pregnancy, when toxoplasmosis can cause miscarriage, or serious complications to the baby, or in an immunocompromised person, when the infection can possibly affect the patient’s eyes or brain. To identify potential drug candidates that could counter toxoplasmosis, we selected 13 compounds which were pre-screened in silico based on the proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In a previous study [24], eight compounds from the COVID Box, which had undergone an in silico screening based on the proteome of T. gondii, were in vitro evaluated against the parasite. Among these compounds, anti-T. gondii activity at the nanomolar range, along with selective activity, was observed only for almitrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study [24], eight compounds from the COVID Box, which had undergone an in silico screening based on the proteome of T. gondii, were in vitro evaluated against the parasite. Among these compounds, anti-T. gondii activity at the nanomolar range, along with selective activity, was observed only for almitrine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, testing this compound against other experimental models of toxoplasmosis would be worthwhile. Based on a molecular docking previously performed [24] almitrine is a strong candidate to bind the Na + / K + ATPase transporter as part of their mechanisms of action. However, further studies are needed to confirm this hypothesis as a possible mechanism of anti-T. gondii action.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, previous researches have showcased the potential of compounds provided by the 'Medicines for Malaria Venture' (MMV) organization for repositioning in the context of toxoplasmosis (Boyom et al, 2014;Spalenka et al, 2018;Cajazeiro et al, 2022;Dos Santos et al, 2023). In this study, the aim was to identify potential compounds from the MMV Pandemic Response Box (PRB) and explore their repositioning against toxoplasmosis using in silico, in vitro and in vivo approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Spalenka et al (2018) and Radke et al (2018) identified, respectively, 25 and 82 Pathogen Box compounds that inhibit T. gondii replication [ 20 , 21 ]. Cajazeiro et al (2022) and Santos et al (2023) demonstrated the activity of COVID Box compounds against T. gondii [ 22 , 23 ]. Pandemic Box compounds were not previously available in Malaria or Pathogen Boxes.…”
Section: Introductionmentioning
confidence: 99%